2012
DOI: 10.1017/s1751731111001613
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of fatty acid esterification and effects of conjugated linoleic acid on glucose homeostasis in pig hepatocytes

Abstract: Conjugated linoleic acids (CLAs) are geometric and positional isomers of linoleic acid (LA) that promote growth, alter glucose metabolism and decrease body fat in growing animals, although the mechanisms are poorly understood. A study was conducted to elucidate the effects of CLA on glucose metabolism, triglyceride (TG) synthesis and IGF-1 synthesis in primary culture of porcine hepatocytes. In addition, hormonal regulation of TG and IGF-1 synthesis was addressed. Hepatocytes were isolated from piglets (n = 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…As supplementation of trans-10,cis-12 CLA, as well as rumen-protected fat, results in a glucose-sparing effect, hepatic gene expression of G6Pase might be a key factor in regulating eGP by reducing glucose delivery to the circulation. Interestingly, CLA treatment decreased gluconeogenesis in porcine hepatocytes, possibly due to increased hepatic insulin sensitivity (Conde-Aguilera et al, 2012). However, it is not clear whether this is also the case in bovine hepatocytes, and, as discussed above, CLA may have not changed insulin sensitivity in our study.…”
Section: Cla Effects On Glucose Metabolismmentioning
confidence: 46%
“…As supplementation of trans-10,cis-12 CLA, as well as rumen-protected fat, results in a glucose-sparing effect, hepatic gene expression of G6Pase might be a key factor in regulating eGP by reducing glucose delivery to the circulation. Interestingly, CLA treatment decreased gluconeogenesis in porcine hepatocytes, possibly due to increased hepatic insulin sensitivity (Conde-Aguilera et al, 2012). However, it is not clear whether this is also the case in bovine hepatocytes, and, as discussed above, CLA may have not changed insulin sensitivity in our study.…”
Section: Cla Effects On Glucose Metabolismmentioning
confidence: 46%
“…Accordingly, Francini et al [52] showed that in Wistar rats given drinking water containing 10% fructose over three weeks, glycogen stores in the liver increased. However, in more advanced stages, the large input of fructose in the liver produces an allosteric negative regulation of the enzyme phosphofructokinase, reducing the uptake of glucose by the liver [53], increasing hepatic gluconeogenesis, and inducing a high intrahepatic accumulation of lipids, which, in turn, occupy a large volume within hepatocytes and disorganize the hepatic structure and functions such as glycogen storage, as well as reducing hepatic IGF-1 synthesis and inducing hepatic IR [50,54]. Our data showing an increase in glycogen stores of the Young – FRU group, unlike the results for the Adult – FRU group, suggest that these groups are at different stages of MS and hepatic IR induced by fructose.…”
Section: Discussionmentioning
confidence: 99%
“…After stunning by electric shock they were exsanguinated and livers were immediately excised, the left lateral lobe removed and transported from the abattoir to the cell culture laboratory in ice cold sterile transport media (Minimum Essential Medium Eagle with Hanks' salts Sigma M9288, 4.46 mM NaCO 3 H, 0.2 mM NaOH) as quick as possible (5 min). Hepatocytes were isolated essentially as published by Conde-Aguilera et al (2012). Viability of isolated hepatocytes from animals was 81.4 ± 4.7% (trypan blue dye exclusion) and cell yield from each liver preparation was 4.9 ± 0.5 × 10 8 viable hepatocytes (n = 18).…”
Section: Isolation Of Liver Cells and Cell Culturementioning
confidence: 99%
“…Protein determination Protein in cell homogenates was determined by a modified Lowry procedure as described by Conde-Aguilera et al (2012). All data were normalized to protein content.…”
Section: Urea Synthesismentioning
confidence: 99%